Reconstructing the Four Cardinal Virtues in Ibn Miskawayh’s Tahdhib Al-Akhlaq for Integrating Classical Islamic Ethics Into Modern Curriculum Design - Ariq Muammar; Edi Suresman; Mulyana Abdullah (JURNAL AT-TURAS, 2026)
Amidst the phenomenon of moral degradation in contemporary educational settings characterized by a crisis of integrity, social-emotional instability, and digital ethics violations existing moral curricula often lack a systematic and conceptually robust ethical framework. This study analytically reconstructs the four cardinal virtues (hikmah, shaja’ah, ‘iffah, and ‘adalah) in Ibn Miskawayh’s Tahdhib al-Akhlaq as a transformative model for modern moral curriculum design. Employing a qualitative content analysis, this textual study systematically evaluates the primary philosophical text alongside contemporary Islamic Religious Education (PAI) curriculum documents (Phases A–F) to assess their conceptual correspondence. The structural mapping reveals that while the current curriculum implicitly internalizes Miskawayh’s virtues across all educational phases, it lacks an explicit, hierarchical ethical formulation. Specifically, the analysis demonstrates that hikmah (wisdom), shaja’ah (courage), and ‘iffah (temperance) function as foundational operational virtues that must be systematically integrated to achieve ‘adalah (justice), which acts as the ultimate meta-virtue and synthesizing goal of character formation. By bridging classical Islamic ethical philosophy with contemporary curriculum theory, this study contributes a conceptually innovative framework that transitions moral education from implicitly normative teachings to a structured and measurable curriculum model. Practically, this reconstructed framework provides actionable guidelines for educational policymakers and curriculum developers to explicitly integrate classical virtue ethics into contemporary pedagogical standards and character education policies.